The Effect of Span to Chord Ratio PBCF on C4-40 Wageningen Series Propeller with CFD Method - Arief, Irfan Syarif; Jadmiko, Edi; Fikry, Izzul (International Journal of Marine Engineering Innovation and Research, 2025)
Propeller boss cap fin is one of the efforts to increase efficiency, especially in the field of ship propulsion. boss cap fins propeller or commonly called PBCF is one of the technologies that replace the boss cap propeller technology that first exists. Increasing efficiency can certainly have an impact on fuel consumption. This study will describe changes in efficiency, thrust, torque and the phenomenon of flow in the propeller after changes in span to chord ratio of fins with a fin form in the form of NACA foil. This research begins with determining the dimensions of the propeller and its model. The next step is to design and draw the boss cap fins propeller by modifying the span to chord ratio of the fins. The final step is analyzing propeller performance with software based on fluid dynamic computation. It is believed that changes in the PBCF span to chord ratio can improve efficiency, thrust, propeller torque, and minimize the hub vortex Simulations are carried out on four variations of the span to chord ratio, namely 0.17, 0.23, 0.29 and 0.34. From this study, it can be concluded that the propeller boss cap fins can increase thrust, torque, and efficiency, but the changes of span to chord ratio PBCF have not much effect on thrust, torque, and propeller efficiency. Increasing the PBCF span to chord ratio can reduce the hub vortex on the propeller.